Public Perceptions and Utilization of Community Pharmacies And Pharmacists: A qualitative study in Indonesia - Muhammad Qowiyul Amin; Tasya Hardina Adha; Anna Wahyuni Widayanti (Asia Pacific Journal of Health Management)
Background: Pharmacists in community pharmacies are essential healthcare providers, offering high-quality and affordable drug services. However, in some countries and notably in Indonesia, they are often wrongly perceived as drug dispensers. This misconception is fueled by a low pharmacist-to-population ratio, limited counselling, and infrequent interactions with pharmacists. Understanding these perceptions is crucial for enhancing pharmacy services and ensuring communities can access quality and affordable healthcare.